1995
DOI: 10.1007/bf00120289
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of hydroxyapatite formed at physiological temperature

Abstract: The mechanical properties of monoliths of calcium-deficient and carbonated hydroxyapatite formed by dissolution-precipitation reactions at 38 °C have been determined. Particulate solid reactants were mixed at liquid-to-solid weight ratios of 0.11 and 0.2 and pressed into various configurations on which mechanical tests were carried out. Testing was performed on wet specimens which had been allowed to react for 8 h by which time phase-pure hydroxyapatite had formed. Calcium-deficient hydroxyapatite produced at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 121 publications
(62 citation statements)
references
References 9 publications
3
56
1
Order By: Relevance
“…10). Even when comparing the 100% HA material, the highest value observed for experimental groups were still about 50% short, which is in agreement with a previous study by Martin and Brown [27].…”
Section: Discussion/conclusionsupporting
confidence: 92%
“…10). Even when comparing the 100% HA material, the highest value observed for experimental groups were still about 50% short, which is in agreement with a previous study by Martin and Brown [27].…”
Section: Discussion/conclusionsupporting
confidence: 92%
“…We observe a certain overestimation of experimental stiffnesses for porosities larger than 0.4 (figure 4), quantified through overall prediction errors of 15.3 ± 15.2% (mean value ± standard deviation according to equation (4.5)), while Poission's ratios are virtually perfectly predicted (−0.2 ± 2.7%; see figure 5). In uniaxial compressive quasi-static tests, a sharp decrease of stress after a stress peak in the stress-strain diagram (Akao et al 1981;Martin & Brown 1995) indicates brittle material failure, as observed for all biomaterials described herein, and the aforementioned stress peak is referred to as the ultimate stress or uniaxial strength S ult,c exp . Respective experimental results are documented for cylindrical samples (Peelen et al 1978) and bars (Akao et al 1981), see table 4 and figure 7.…”
Section: (E) Comparison Between Biomaterial-specific Stiffness Predicmentioning
confidence: 69%
“…Although the bending strength values reported for CPCs are typically in the range of 5-15 MPa (Martin & Brown 1995;Ginebra et al 2001), close to that of trabecular bone (estimated between 10 and 20 MPa) (Barinov 2010), their strain to failure is much lower . The brittleness of CPCs has recently been highlighted in a report on their strain-to-crack-initiation, which amounted to a mere 0.2% in compression (Ajaxon et al 2017).…”
Section: Introductionmentioning
confidence: 83%